Fabrication of InGaP high electron mobility transistors by electron beam technique - Gay, Boon Ping. (2008)
Recently, there has been great interest in the development of the InxGa|.xP material system as an alternative to AlyGai_yAs, for applications, such as in high electron mobility transistors, heterojunction bipolar transistors and diode lasers. This is attributed to the several advantages that InxGai.xP has over AlyGai.yAs. InxGai_xP does not appear to exhibit problems with donor-related deep traps, which can cause instabilities in the threshold voltage and transconductance of the transistor. In addition, the InxGai_xP/GaAs heterointerface has been shown to have a low carrier recombination velocity, and can be selectively wet etched in HCl-based solutions. Therefore, this thesis presents the device fabrication and characterisation of the InxGai.xP/In0.2oGao.8oAs HEMT.